Productivity and Policy in Higher Education. (3rd June 2019) - Moore, Kenneth; Croucher, Gwilym; Coates, Hamish
Abstract: Understanding and improving the performance of public higher education institutions is a matter of growing interest to university and government leaders. To this end, this article surveys dimensions of recent approaches to productivity measurement in higher education, illustrating trends, limitations and developments, and exemplifies these with reference to Australian universities. The article closes by discussing policy considerations that would help augment the design of policy, making comment on the implications for performance‐incentivised funding of higher education .